NILAI-NILAI PENDIDIKAN ISLAM DALAM SURAT AL-FATIHAH - Rofi'atul Ummah; Devi Habibi Muhammad; Ari Susandi (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2021)
The purpose of this study is to analyze the content of the Qur'an contained in Surat Al-Fatihah related to the values of Islamic Education contained in it. This research method uses qualitative methods with data collection in a literature study. This type of research is literature (library reseach) and uses a philosophical approach that is to see the value of Islamic Education contained in surat Al-fatihah. The data sources used are from a variety of literature such as books, scientific papers (journals, thesis). The results of research including 1) aqidah education (tauhid) 2) Sharia education 4) Education akhlak 5) Education history story.